The effects of the energy transition on power sector employment in Latin America - David López; Mariana Weiss; Jose Francisco Moreira Pessanha; Karla Arias; Livia Gouvea Gomes; Michelle Hallack (Inter-American Development Bank (IDB), 2023)
The present study analyzes the relationship between energy transition and job creation potential in Latin America. It looks at companies' characteristics to infer potential hiring process drivers in forthcoming years. The analysis is based on an econometric model applied to cross-sectional data to explain the dependent variable "potential hiring rate" depending on the firm's size (based on the number of clients), area of activity or technology, employees' educational levels, and labor policies. The data came from 338 interviewed companies, including energy generation, transmission, distribution, and new energy services, oil and gas, and construction companies in six Latin American Countries (Bolivia, Chile, Costa Rica, Mexico, Panama, and Uruguay). The econometric study focused on 135 companies that declared they would be hiring new employees in the next year when they were interviewed. The results show that the smaller energy companies with a larger participation of skilled workforce will tend to have a higher expected hiring rate in the forthcoming year, implying an inverse relationship between firm size and potential hiring rate. The model findings convey that the higher the number of skilled employees in the workforce, the greater the expected expansion of the company's labor force, particularly in renewable generation companies. Another aspect worth considering about the factors behind the company's potential hiring rate is the question of job quality. The results suggest that the firms hiring more are those with fewer policies. It can be explained by the fact that more traditional companies, such as hydrocarbon and utility companies, tend to have better-established policies but necessarily the highest potential job creation rates. This takeaway raises a discussion about whether a change in job quality is associated with the energy transition or merely with new entrants who will become traditional in the coming years. Moreover, it also helps to explain some of the political economies of the labor market that may play a role in the energy transition process. Therefore, one of the present study's main takeaways is the need to analyze more in-depth and promote job quality in smaller energy companies.
Keywords: L25; D25; M51; Q40; Q42; 330; Firm's Job creation; Energy Transition; Post-Covid Economic Recovery; LatinAmerica; Industrial Organization